Peculiarities of properties of the pulse plasma jet - Podzirey, Yu.S.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2016)
On the basis of the detonation of the fuel cycle it is considered the possibility of a flat pulsed plasma jet designed to feed into the optical resonator of the TEA laser to the heat pump. There is a schematic diagram of a device for the production of a flat plasma jet. It is shown that the using of detonation fuel cycle leads to greater population inversion of the upper levels. Because of that the possibility is achieved to perform the TEA laser, combining both the high average and peak power.